The Phenomenon Of Studying Assignment Joking In Social Studies Study Program Students At Fatmawati Sukarno State Islamic University Bengkulu - Neti Adelia; Lena Meutiah Febrian; Moch Iqbal; Sepri Yunarman; Delta Fitrianah (Yayasan Azhar Amanaa Yogyakarta, 2026)
Coursework jockeying is a form of academic cheating that is increasingly developing in the university environment along with the advancement of information technology and ease of access to academic service providers. This phenomenon not only reflects the low academic integrity of students, but also shows the existence of various factors that affect students' decisions to use jockey services in completing lecture assignments. This study aims to describe the forms of practice of jockey for lecture assignments and analyze the factors that encourage students of the Social Sciences Study Program of UIN Fatmawati Sukarno Bengkulu to use the services of task jockeys. The research uses a qualitative approach with a descriptive type of research. The research informants consist of students who use jockey services, jockey service providers, and lecturers as supporting informants. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that jockeying practices are carried out on various types of tasks, such as papers, scientific articles, presentations, and observation reports. Factors that encourage students to use jockey services include difficulty completing assignments, time limitations, high academic load, and ease of obtaining jockey services through social media. This phenomenon shows that jockeying practices are not only influenced by individual factors, but also by academic culture and the development of digital technology. Therefore, it is necessary to strengthen academic ethics, increase lecturer supervision, and more strict institutional policies to prevent the practice of jockeying in the university environment.